2021
DOI: 10.51936/tip.58.1.28-48
|View full text |Cite
|
Sign up to set email alerts
|

Prekarizacija Standardnega in Nestandardnega Zaposlovanja v Sloveniji (2005–2019)

Abstract: Povzetek. Namen članka je opredeliti trende in razsežnosti prekarizacije standardnega in nestandardnega zaposlovanja v Sloveniji med gospodarsko depresijo in njegovo ponovno ekspanzijo. V literaturi so pojmi (ne)standardno, prekarno in neformalno delo nejasno definirani in slabo razločeni, zato jih najprej teoretsko začrtamo. Nato analiziramo spreminjanje sestave delovne sile v obdobju 2005–2019, kakor jo pokaže statistična analiza longitudinalnih mikropodatkov iz ankete Aktivno in neaktivno prebivalstvo (SURS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
0
0
2
Order By: Relevance
“…Firstly, TAW agencies were discouraged from using fixed-term contracts for posted workers by introducing several benefits for employing workers on an indefinite basis, such as exempting these workers from the client organizations' quota, offering lower social contribution payments, and ensuring compensation between placements. By differentiating the rights and obligations that agencies had for workers on fixed-term versus indefinite-term contracts, the legislator reversed the fixed-term employment for posted workers, especially after the enactment of the ZDR-1 and the ZUTD-C in 2013 (Breznik 2018). Secondly, compensation for posted workers between placements, introduced in 2002, has only increased with subsequent amendments (in 2013 with the ZDR-1 and in 2023 with the ZDR-1C).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Firstly, TAW agencies were discouraged from using fixed-term contracts for posted workers by introducing several benefits for employing workers on an indefinite basis, such as exempting these workers from the client organizations' quota, offering lower social contribution payments, and ensuring compensation between placements. By differentiating the rights and obligations that agencies had for workers on fixed-term versus indefinite-term contracts, the legislator reversed the fixed-term employment for posted workers, especially after the enactment of the ZDR-1 and the ZUTD-C in 2013 (Breznik 2018). Secondly, compensation for posted workers between placements, introduced in 2002, has only increased with subsequent amendments (in 2013 with the ZDR-1 and in 2023 with the ZDR-1C).…”
Section: Discussionmentioning
confidence: 99%
“…The case study approach was selected for its capacity to examine the identified variables in their actual context from diverse perspectives (Neuman 2014;Webley 2016). Slovenia was chosen due to the continuous and rapid evolution of the TAW model in the country, despite the presence of relatively strict labour laws, ongoing legislative reforms, and stringent, yet challenging enforcement (Breznik and Čehovin Zajc 2021).…”
Section: Methodology and Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Iz različnih analiz in raziskav (Kanjuo Mrčela in Ignjatovič, 2015;Grimshaw at al., 2016;Broughton, 2016;ILO, 2016;Breznik in Čehovin Zajc, 2021) je mogoče izluščiti tudi jasne trende glede deleža nestandardnih oblik zaposlitve v Sloveniji. V zadnjih desetih oz.…”
Section: Nestandardne Oblike Dela V Slovenijiunclassified